Oporto newspapers and the city readers. The construction of editorial and audiences identities - Lima, Helena (RIHC. Revista Internacional de Historia de la Comunicación, 2013)
The three Oporto daily newspapers O Comércio do Porto, O Primeiro de Janeiro and Jornal de Notícias were founded during the XIX century and steadily grew in prestige and respect amongst the national Portuguese press. These papers began as local and ideological projects supported by political parties and a powerful commercial association but gradually evolved to more comprehensive newspapers with a wider range of lectors. Each particular profile was built through editorial policies which led to strategies of audience identification, underlined by the charisma of their owners and directors. The aim of this study is to identify the engagement processes with readers in their early days and the methodology will rely on sources such as newspapers contents and some other specialized publications. The key moments of evolution in Comércio, Janeiro and Notícias will be tracked by the adaptation to the modernization challenges according to reports, newspapers and some senior journalists’ testimonies.